Navigating the maze of osteoarthritis treatment: A qualitative study exploring the experience of individuals with osteoarthritis in Tasmania, Australia. (12th September 2022) - Sutton, Laura; Jose, Kim; Hansen, Emily; Laslett, Laura; Makin, Jennifer; Winzenberg, Tania; Balogun, Saliu; Aitken, Dawn
Abstract: Objective: Using a qualitative design this study aimed to (1) explore the experience of people living with osteoarthritis (OA), (2) gain an understanding of their navigation of the health system and, (3) explore their opinions on the role of exercise and joint replacement surgery for the management of OA. Methods: Purposive sampling was used to recruit 26 participants with knee OA, aged 45 years and over, from Tasmania, Australia. Semi‐structured interviews were audio‐recorded, transcribed, coded, and thematically analysed to document participant understanding and experience of OA and their opinions on the role of exercise and surgery in managing OA. Results: Of the 26 participants, 80% ( n  = 21) were female with a mean age of 66 years. The main theme identified was that individuals with knee OA were navigating a maze of OA treatments. Three related subthemes were that participants: (i) perceived their general practitioner did not have an ongoing role in their OA care, (ii) self‐directed their management and, (iii) sampled from a 'smorgasbord' of treatment options, including low‐value care options. Two other major themes were: the role of exercise for OA management, and surgery as a last resort. Conclusion: Our findings suggest that OA patients may not be choosing consistent, high‐value care for their OA. This highlights the importance of an evidence‐based multi‐disciplinary approach to guide patients to self‐manage their OA and support their navigation of the health system. Reducing emphasis on the pathway to surgery and streamlining access to conservative management strategies may assist people to receive high‐value care.